Prenatal Irradiation-Induced Hippocampal Abnormalities in Rats Evaluated Using Manganese-Enhanced MRI - Saito, Shigeyoshi; Sawada, Kazuhiko; Aoki, Ichio (Frontiers in Neural Circuits, 2018)
The aim of this study was to characterize hippocampal abnormalities in rats after prenatal x-ray irradiation using manganese-enhanced MRI (MEMRI). All radiation-exposed rat brains showed a reduced volume with prominent dilatation of lateral ventricles. Moreover, MEMRI-enhanced areas within the hippocampus were reduced in volumes by approximately 25% of controls, although the entire volume of hippocampus was decreased by approximately 50% of controls. MEMRI signals were enhanced strongly in the hilus and granular layer of the dentate gyrus (DG) and the pyramidal layer and infrapyramidal region of the CA3 region, and moderately along the CA1/2 pyramidal cell layer in the control rats. In radiation-exposed rats, MEMRI signals in the CA1/2 regions disappeared due to disrupting their laminar organization, although strong MEMRI signals were sustained in the DG and CA3 regions. Histopathological examinations in radiation-exposed rats revealed disorganizations of the DG granule cell layer and the CA3 pyramidal cell layer with reducing the cell density. The CA1/2 pyramidal cell layer was disrupted by invading ectopic cell mass. Neural cell adhesion molecule (NCAM)-positive fiber bundles were sustained in radiation-exposed rats, although they distributed aberrantly in the suprapyramidal CA3 region with a slight reduction of NCAM staining. Furthermore, glial components consisted largely by astrocytes and minor by microglia were densely distributed in the DG rather than in other hippocampal regions, and their density radiation-exposed rats. In conclusion, MEMRI signal enhancements could delineate different neuronal and/or glial components among hippocampal regions. We characterized microstructures of the deformed hippocampus as well as its macrostructures in a prenatally radiation-exposed rat model using in vivo MEMRI. The present findings provide advantageous information for detecting nondestructively hippocampal deformations in neurodevelopmental disorders.